Histological Inflammation in the Endoscopically Uninflamed Mucosa is Associated With Worse Outcomes in Limited Ulcerative Colitis. Issue 3 (17th May 2021) - de Frias Gomes, Catarina Geraldes; de Almeida, Alexandra Sofia Ribeiro; Mendes, Catarina Callé Lucas; Ellul, Pierre; Burisch, Johan; Buhagiar, Tiffany; Attard, Abigail; Lo, Bobby; Ungaro, Ryan C; da Silva Morão, Bárbara Tonilhas; Gouveia, Catarina Ferreira; de Carvalho e Branco, Joana Milheiro Delgado; et al.
Abstract: Background: The Montreal classification categorizes patients with ulcerative colitis (UC) based on their macroscopic disease extent. Independent of endoscopic extent, biopsies through all colonic segments should be retrieved during index colonoscopy. However, the prognostic value of histological inflammation at diagnosis in the inflamed and uninflamed regions of the colon has never been assessed. Methods: This was a multicenter retrospective cohort study of newly diagnosed patients with treatment-naïve proctitis and left-sided UC. Biopsies from at least 2 colonic segments (endoscopically inflamed and uninflamed mucosa) were retrieved and reviewed by 2 pathologists. Histological features in the endoscopically inflamed and uninflamed mucosa were scored using the Nancy score. The primary outcomes were disease complications (proximal disease extension, need for hospitalization or colectomy) and higher therapeutic requirements (need for steroids or for therapy escalation). Results: Overall, 93 treatment-naïve patients were included, with a median follow-up of 44 months (range, 2-329). The prevalence of any histological inflammation above the endoscopic margin was 71%. Proximal disease extension was more frequent in patients with histological inflammation in the endoscopically uninflamed mucosa at diagnosis (21.5% vs 3.4%, P  = 0.04). Histological involvement above the endoscopic margin was the only predictor associated with an earlier need for therapy escalation (adjusted hazard ratio, 3.69; 95% confidence interval, 1.05-13.0); P  = 0.04) and disease complications (adjusted hazard ratio, 4.79; 95% confidence interval, 1.10-20.9; P  = 0.04). Conclusions: The presence of histological inflammation in the endoscopically uninflamed mucosa at the time of diagnosis was associated with worse outcomes in limited UC.